CHALLENGES OF IMPLEMENTING ARTIFICIAL INTELLIGENCE IN CADET TRAINING - Kravchenko, Oksana; Safin, Oleksandr; Mas, Natalia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . This article is devoted to the study of possible risks and challenges in the training of cadets within the system of higher military education that arise from the rapid implementation of technology, where artificial intelligence (AI) and neural network technologies are already part of its structure. The analysis is conducted to forecast the future nature of cadet training in the higher military education system, as well as to explore paradigm shifts in teaching under the influence of AI.M e t h o d s . Content analysis of scientific sources of information, comparison, systematisation, classification, generalisation.R e s u l t s . The article outlines a number of anticipated problems that may arise in the cadet training, in the pedagogical process, in the organisation of independent work, as well as in the management and administration of higher education institutions when implementing AI capabilities in the educational process. The issue of the impact of limitations on the development of military education is considered, namely the detrimental consequences in the case of monopolization of AI algorithms and the subjective management of neural networks by technocratic groups. In analyzing the intersections of opposing issues, problematic aspects, and the positive dynamics of AI's influence on higher education, a direction for further research on this issue in the military educational environment is identified.C o n c l u s i o n s . The article examines the rapidly developing technologies of artificial intelligence aimed at supporting human cognition. The main achievements, emerging challenges, and promising development paths are outlined. It is argued that although AI technologies are directed toward humans and promise greater psychological comfort, they also pose serious risks. It is proposed to focus on the concept of ‘digital angels', understood as AI technologies created to protect the interests of their owner. Digital angels should combine three roles: digital assistants that help people organize their lives; digital communicators that enable interaction with other people and the environment; and digital confidants that people can trust unconditionally.
Keywords: higher education; artificial intelligence; monopolization of decisions; optimization; pedagogical technologies; teaching; digitalisation